A study of customer satisfaction towards Telekom Malaysia Berhad (TM) in Kota Kinabalu, Sabah / Rusydi Rosli - Rosli, Rusydi (2012)
Telekom Malaysia Berhad(TM), the national communications and multimedia provider and larger telecommunications company in Malaysia, is now in the fourth. Telekom Malaysia Berhad (TM), Malaysia's broadband champion and leading integrated information and communications group, offers a comprehensive range of communication services and solutions in broadband, data and fixed-line. As a market leader, TM is driven by stakeholder value creation in a highly competitive environment. The Group places emphasis on delivering an enhanced customer experience via continuous customer service quality improvements and innovations, whilst focusing on increased operational efficiency and productivity. Leveraging on our extensive global connectivity, network infrastructure and collective expertise, TM is well positioned to propel Malaysia as a regional Internet hub and digital gateway for South-East Asia. TM remains steadfast in its transformation into a new generation communications provider to deliver an enhanced and integrated digital lifestyle to all Malaysians, and opening up possibilities through connection, communication and collaboration, towards our shared vision of elevating the nation into a high - income economy.